PENGEMBANGAN BIG BOOK SEKOLAH DASAR - Mahmud Alpusari; Eva Astuti Mulyani; Riki Apriyandi Putra; Neni Hermita (Tunjuk Ajar: Jurnal Penelitian Ilmu Pendidikan, 2021)
This study aims to assist teachers in developing learning media in elementary schools, namely the big book. This study uses a developmental research type with the Thiagarajan 4-D Model which consists of 4 stages, namely, define, design, develop, and disseminate. The research was conducted at PGSD of FKIP, Universitas Riau. The object of this research is the big book of elementary school students developed from the basic competencies in the 2013 curriculum. The products produced are 3 big books with the title Sekolahku, Wisata ke Pantai and Taman Kota. The results of the validation of the three big book titles carried out by experts, the feasibility of the content of the material obtained by the percentage of scores for the title Sekolahku 82.1%; Wisata ke Pantai 82.1%; and Taman Kota 86%. Meanwhile, for the big book language assessment, the percentage for Sekolahku was 79.9%; Wisata ke Pantai 79.7%; and Taman Kota 82.5%. So that the big book learning media is feasible to be tested with revisions according to suggestions.